Antioxidant and photoprotective role of latex C-serum from Hevea brasiliensis during 15-week UVB irradiation in male hairless SKH-1 mice - Kerche, Leandra E. [UNESP]; Carrara, Iriana M.; Marinello, Poliana C.; Cavalcante, Dalita G.S.M. [UNESP]; Danna, Caroline S. [UNESP]; Cecchini, Rubens; Cecchini, Alessandra L.; Job, Aldo E. [UNESP] (Taylor & Francis, 2023)
It is known that UVB radiation induces several adverse skin alterations starting from simple photoaging to skin cancer. In addition, it was demonstrated that reactive oxygen species (ROS) were found to be related to cancer development and progression. The aim of study was to examine whether male hairless (SKH-1) mice (Mus musculus) that were subchronically exposed to UVB radiation presented with actinic keratosis (AK) and squamous cell carcinoma lesions, and that treatment with latex C-serum cream significantly prevented abnormal skin development. Data demonstrated for the first time the photoprotective activity of latex C-serum extracted from the rubber tree Hevea brasiliensis var. subconcolor Ducke. Latex C-serum prevented the progression of AK to squamous cell carcinoma in SKH-1 mice, indicating that mice topically treated with latex C-serum presented only AK lesions and treatment with the highest concentration (10%) significantly reduced epidermal thickness, suggesting diminished cell proliferation. Latex C-serum protected the skin of mice against oxidative stress damage, increasing catalase (CAT) activity, regenerating glutathione (GSH) levels, lowering thiobarbituric acid-reactive species (TBARS) production and regenerating the total antioxidant capacity (TAC) of the skin. Evidence that UV radiation in skin induced systemic alterations and erythrocytic analysis indicated that latex C-serum increased CAT activity and GSH levels. Taken together these data indicate that latex C-serum plays an important antioxidant and photoprotective role, preventing serious damage to the skin following exposure to UVB radiation.
Keywords: antioxidant; Hevea brasiliensis; oxidative stress; squamous cell carcinoma; UVB radiation